2017
DOI: 10.1121/1.5017522
|View full text |Cite
|
Sign up to set email alerts
|

Self-masking and overlap-masking from reverberation using the speech-evoked auditory brainstem response

Abstract: This study introduces an improved method to investigate the effects of reverberation using the speech-evoked auditory brainstem response (ABR) that more realistically captures the influence of self- and overlap-masking induced by room reverberation. Speech-evoked ABR was measured under three acoustic scenarios: anechoic, mild reverberation with dominance of early reflections, and severe reverberation with dominance of late reverberation. Responses were significantly weaker and had longer latencies with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…But why is a similar desynchronization to speech not observed in reverberation? Animal recordings (Sayles and Winter, 2008) and previous human FFR studies (Al Osman et al, 2017; Bidelman and Krishnan, 2010) show that speech cues are more easily maintained at the neural level in 15 reverb compared to noise (for review, see Bidelman, 2017). Some investigators have also postulated that neurons in the brainstem inferior colliculus—the putative generator of scalp FFRs (Bidelman, 2018; Smith et al, 1975)—might perform a neural compensation that mitigates the negative effects of reverb and target signal representations (Slama and Delgutte, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…But why is a similar desynchronization to speech not observed in reverberation? Animal recordings (Sayles and Winter, 2008) and previous human FFR studies (Al Osman et al, 2017; Bidelman and Krishnan, 2010) show that speech cues are more easily maintained at the neural level in 15 reverb compared to noise (for review, see Bidelman, 2017). Some investigators have also postulated that neurons in the brainstem inferior colliculus—the putative generator of scalp FFRs (Bidelman, 2018; Smith et al, 1975)—might perform a neural compensation that mitigates the negative effects of reverb and target signal representations (Slama and Delgutte, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we examined concurrent vowel processing in different levels of noise interference (quiet vs. +5 dB SNR) to evaluate how the neural encoding of spectro-temporal cues is affected by noise at a subcortical level. Despite ample FFR studies using isolated speech sounds (e.g., vowels, stop consonants) (Al Osman et al, 2017; Anderson and Kraus, 2010; Bidelman and Krishnan, 2010; Hornickel et al, 2009; Krishnan, 2002; Parbery-Clark et al, 2009b), to our knowledge, this is the first to examine brainstem encoding of concurrent speech mixtures in human auditory system using FFRs.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that speech-evoked brainstem and early cortical responses were degraded more by noise than reverberation. Previous physiological studies (Al Osman et al, 2017;Bidelman & Krishnan, 2010;Sayles & Winter, 2008) have also shown better preservation of neural representation in reverberation compared to noise (Bidelman, 2017, review). It remains unclear if these differences simply reflect fundamental differences in the extent to which spectrotemporal pitch-relevant acoustic features are disrupted and/or the relative effectiveness of masking mechanisms under both noise and reverberation.…”
Section: Experience-dependent Enhancement In Pitch Representation Is mentioning
confidence: 89%